RANCANG BANGUN SISTEM PERPUSTAKAAN DESA NGADIRGO BERBASIS WEB - SEPTIAWAN, CATUR; TRI HANDOKO, DRS.,M.KOM, WIDIYANTO (Information Technology and Telematics, 2018)
Abstract- Currently Ngadirgo village library still uses a catalog system printed on the paper in the form of a catalog card, so to get information about the library books will be very much in need of energy and time. The lending system also uses a record-keeping system in the form of membership cards, so it will spend a lot of time and energy in the event of book borrowing past due time, certain return of books, or many books borrowed, it will require the search process and the process of tabulation of data long enoughSystem development method used in this research is Waterfall, system design using UML and system implementation using PHP and MySQL.The results of this research are Ngadirgo web-based library system can be used to manage the recording of borrowing transactions or the return of books and the making of reports required by Ngadirgo village library. Keywords – Ngadirgo Village Library, Lending, PHP, MySQLDAFTAR PUSTAKA Aditya, A.N, (2010), Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, Bekasi Arianto, M.F, (2014), Rancang Bangun Sistem Informasi Perpustakaan, Skripsi, Universitas Narotama Surabaya Bafadal, I., (2008), Manajemen Perlengkapan Sekolah, Bumi Aksara, Jakarta Irawan, Y., (2011), Perancangan Sistem Informasi Perpustakaan Berbasis Web Application, Skripsi, Universitas Diponegoro Semarang Kusumatuti, F., (2012), Aplikasi Perpustakaan Online Berbasis Android Dan PHP Menggunakan Protokol JSON, Skripsi, Universitas Gunadarma Prasetyo, D.D, (2006), Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta. Presman, R.S., (2006), Rekayasa Perangkat Lunak Pendekatan Praktisi (Buku. Satu), Andi, Yogyakarta Republik Indonesia, (2007). Undang-Undang Republik Indonesia Nomor 43 Tahun 2007 tentang Perpustakaan, Jakarta Supriyanto, A, (2005), Pengantar Teknologi Informasi, Salemba Infotek, Jakarta Sutopo, A.H, (2006), Analisis dan Desain Berorientasi Objek, J & J Learning, Yogyakarta Whitten, J.L. (2004), Metode Desain dan Analisa Sistem, Andi Offset, Yogyakarta